COVID-19 in rural Malawi: Perceived risks and economic impacts round 2 - Ambler, Kate; Herskowitz, Sylvan; Maredia, Mywish K.; Mockshell, Jonathan (International Food Policy Research Institute, 2021)
This note summarizes perceptions of COVID-19 impacts and risks from a panel phone survey of rural households in eight districts in rural Malawi. While the results from the first round conducted in August 2020 were reported in a previous brief, this note will focus on the evolution of indicators from round 1 to round 2, conducted in November 2020. The sample comprises 833 households interviewed in both survey rounds. Two additional follow-up survey rounds are planned for 2021. The survey was originally designed to measure the seasonality of labor activities but was adjusted to assess COVID-19 impacts and perceptions in rural Malawi. Though initial concern of the impact of COVID-19 on Malawi was high at the start of the global pandemic, case numbers stayed relatively low through the end of 2020. Seven-day averages of 50-100 cases during the first survey round had dropped to under 5 in the fourth quarter of the year. Our analysis will examine how people’s perceptions evolved during this period of low infections.